Insolvency Risk: Issues and Challenges for Public Sector Commercial Banks of India - Chandra, Salil; Awasthi, Richa (Indian Journal of Finance, 2019)
This paper thoroughly examined the insolvency risk of four major commercial banks of India namely, State Bank of India, Punjab National Bank, Bank of Baroda, and Canara Bank during the period from 2005-06 - 2017-18 and scrutinized whether the regulatory capital requirement as per the Reserve Bank of India norms was enough to insulate commercial banks from the potential threat of insolvency risk. Moreover, the impact of the main determinants on the parameter used to measure insolvency risk namely, Z-score was also analyzed. Our study clearly showed that the insolvency risk of all these banks increased significantly since the value of Z-score dipped substantially overtime. Further, the analysis also revealed that the current level of regulatory capital of the banks was not enough to overcome the potential threat of insolvency risk. Finally, percentage of nonperforming assets to total advances pertaining to the industrial sector was found to be an important determinant that aggravated the insolvency risk of banks. All these findings clearly highlighted that it is not the opportune time for the Reserve Bank of India to ease-off the regulatory capital norms regarding the capital risk adequacy ratio (CRAR). Besides, there is an urgent need for commercial banks to improve the quality of lending pertaining to the industrial sector of the economy along with stepping up their credit business regarding the personal loan segment. Moreover, too much government intervention distorts the automatic functioning of financial institutions. Rather, a mechanism should be devised to make these institutions more accountable.